The impact of vowels on the change of phonetic features: a study of Surah At-Takwir according to the Warsh recitation. - bouras, imane; Chegoufi, Rached (El Omda in Linguistics and Discourse Analysis, 2023)
This research paper deals with the effect of short vowels in changing the qualities of sounds in the narration of Warsh. This study aims to identify the most important features of sounds in Surat At-Takwir, as well as the effect and role of short vowels in changing the qualities of some sounds in Surat At-Takwir with the narration of Warsh. The most important findings are that the letters "L" and "R" are large if they are preceded by "a " or "o", and they are spotted if they are preceded by "i". Also, the most important characteristic of the sounds of letter is the diversity between strength and weakness. The aperture vowel " a" is the highest and the " i " and " o" .